Food-Specific Inhibitory Control Mediates the Effect of Disgust Sensitivity on Body Mass Index - Liu, Xing; Li, Ji; Turel, Ofir; Chen, Rui; He, Qinghua (Frontiers in Psychology, 2019)
Disgust is an emotion that drives food avoidance. People vary in their responses to disgust, which is captured by their disgust sensitivity. Disgust sensitivity is clinically significant because it can influence eating behaviors and indirectly people’s body-mass index (BMI). Inhibitory control can also influence BMI through the role that such reflective abilities play in governing food intake. In this study, we relied on neural models of disgust to suggest that disgust and inhibitory control are intertwined, and that inhibitory control facilitates the translation of disgust sensitivity into BMI. Mediation analyses applied to 46 subjects, including 29 with normal body weight (BMI=18.34 kg/m2 (SD=1.58)) and 17 overweight/obese (BMI=26.03 kg/m2 (SD=2.58)) were used to test the hypothesis. Subjects completed the Chinese version of Disgust Scale-Revised, and an inhibition control test (Food-specific Stop-Signal Task). There were negative correlations between disgust sensitivity score (DS) and body mass index (BMI), and between DS and stop signal reaction time (SSRT). Moreover, BMI was positively correlated with SSRT. The mediation model results showed that disgust sensitivity was associated with BMI and that this relationship was mediated via inhibition control. There was no significant effect of DS on BMI, while the effect of SSRT on BMI was significant. This suggested that the effect of disgust sensitivity on BMI was fully mediated through food-specific inhibitory control. This supported our hypothesis that body mass index was affected by disgust sensitivity and that this relationship was mediated by inhibition control. These findings revealed a key mechanism that underlies the disgust sensitivity – BMI association, and pointed to future research and potential interventions aimed at food intake management.